Intestinal alkaline phosphatase at the crossroad of intestinal health and disease – a putative role in type 1 diabetes. (10th April 2017) - Lassenius, M. I.; Fogarty, C. L.; Blaut, M.; Haimila, K.; Riittinen, L.; Paju, A.; Kirveskari, J.; Järvelä, J.; Ahola, A. J.; Gordin, D.; Härma, M.‐A.; Kumar, A.; et al.
Abstract: Background: Patients with type 1 diabetes have shown an increase in circulating cytokines, altered lipoprotein metabolism and signs of vascular dysfunction in response to high‐fat meals. Intestinal alkaline phosphatase (IAP) regulates lipid transport and inflammatory responses in the gastrointestinal tract. We therefore hypothesized that changes in IAP activity could have profound effects on gut metabolic homeostasis in patients with type 1 diabetes. Methods: Faecal samples of 41 nondiabetic controls and 46 patients with type 1 diabetes were analysed for IAP activity, calprotectin, immunoglobulins and short‐chain fatty acids (SCFAs). The impact of oral IAP supplementation on intestinal immunoglobulin levels was evaluated in C57BL/6 mice exposed to high‐fat diet for 11 weeks. Results: Patients with type 1 diabetes exhibited signs of intestinal inflammation. Compared to controls, patients with diabetes had higher faecal calprotectin levels, lower faecal IAP activities accompanied by lower propionate and butyrate concentrations. Moreover, the amount of faecal IgA and the level of antibodies binding to oxidized LDL were decreased in patients with type 1 diabetes. In mice, oral IAP supplementation increased intestinal IgA levels markedly. Conclusion: Deprivation of protective intestinal factors may increase the risk of inflammation in the gut – a phenomenon that seems to be present already in patients with uncomplicated type 1 diabetes. Low levels of intestinal IgA and antibodies to oxidized lipid epitopes may predispose such patients to inflammation‐driven complications such as cardiovascular disease and diabetic nephropathy. Importantly, oral IAP supplementation could have beneficial therapeutic effects on gut metabolic homeostasis, possibly through stimulation of intestinal IgA secretion.